William Plomer's and Sol Plaatje's South Africa: art as vision and reality - Ogu, Memoye Abijah (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1995)
This thesis essays a comparative study of William Plomer's Turbott Wolfe (1925) and Sol Plaatje's Mhudi (1930). Although writing from very different subject positions within the social order of the time, Plomer and Plaatje embody in their novels a strikingly similar vision of a South Africa free of racial barriers. Plaatje's version of South African history in Mhudi deconstructs colonial binarism by dramatizing not only conflict and difference but also co-operation and commonality. Holding the past up as a mirror to the present, it protests against racial injustice while implying the continuing possibility of reconciliation. Plomer reacts angrily to white hypocrisy and insists on the rights and humanity of his African characters, in the name of imperatives both moral and political. He seeks additional sanction for these by situating the South African race questioning the context of a Western world slowly awakening to the consequences of modernity. During a time of political turbulence, both writers speak out boldly and confidently against the rising dominance of segregationist ideology. The imminent inception of full democracy in South Africa has reanimated the relevance of these writers' vision of a non- racial social order. If one of the challenges facing the South African literary historian 'today is the reconstruction of a truly national literary tradition, then Mhudi and Turbott Wolfe would appear to be key works in such an enterprise. As different as Plaatje's epic myth-making is from Plomer's modernist irony, both novels contrive to speak with a new voice: a national voice which expresses the aspirations of all South Africa's people. They are, moreover, novels whose survival seems guaranteed as much by their aesthetic qualities as by their ideological orientation. The novels are examined against the backgrounds of South African society and colonial literary production. They are seen as milestones in the development of a liberal South African literary tradition. By breaking with the dominant oppositional mode, whether that of "white writing" or an emergent "writing black", Plomer and Plaatje exemplify a literature at once socially relevant and possessed of a prophetic vision that remains of significance in South Africa today.
Keywords: Plaatje, Sol. T. (Solomon Tshekisho), 1876-1932. --Mhudi; Plomer, William, 1903-1973 -- Turbott Wolfe; Race in literature